Increased core body temperature in astronauts during long-duration space missions - Stahn, Alexander C; Werner, Andreas; Opatz, Oliver; Maggioni, Martina A; Steinach, Mathias; von Ahlefeld, Victoria Weller; Moore, Alan; Crucian, Brian E; Smith, Scott M; Zwart, Sara R; Schlabs, Thomas; Mendt, Stefan; et al. (Scientific reports, 2017)
Humans' core body temperature (CBT) is strictly controlled within a narrow range. Various studies dealt with the impact of physical activity, clothing, and environmental factors on CBT regulation under terrestrial conditions. However, the effects of weightlessness on human thermoregulation are not well understood. Specifically, studies, investigating the effects of long-duration spaceflight on CBT at rest and during exercise are clearly lacking. We here show that during exercise CBT rises higher and faster in space than on Earth. Moreover, we observed for the first time a sustained increased astronauts' CBT also under resting conditions. This increase of about 1 °C developed gradually over 2.5 months and was associated with augmented concentrations of interleukin-1 receptor antagonist, a key anti-inflammatory protein. Since even minor increases in CBT can impair physical and cognitive performance, both findings have a considerable impact on astronauts' health and well-being during future long-term spaceflights. Moreover, our findings also pinpoint crucial physiological challenges for spacefaring civilizations, and raise questions about the assumption of a thermoregulatory set point in humans, and our evolutionary ability to adapt to climate changes on Earth.
Keywords: tělesná teplota; časové faktory; Weightlessness; kosmonauti; Astronauts; stav beztíže; Humans; Space Flight; Time Factors; lidé; kosmický let; Body Temperature